Effect of Chitosan-TiO2 Membrane Performance for the Degradation of Batik Waste with a Photocatalytic Hybrid System - Nyamiati, Retno Dwi; Timotius, Daniel; Sri Rahmawati, Septi Sri; Carissavila, Calista; Amalia, Noor (Eksergi, 2024)
The treatment of industrial wastewater has gained significant attention in recent years due to its detrimental impact on the environment and public health. This study aims to explore the effectiveness of a photocatalytic hybrid system using a Chitosan-TiO2 membrane for the degradation of batik waste. The performance of the membrane was investigated through a series of experiments, evaluating its ability to remove organic pollutants and enhance the overall treatment efficiency. The morphology, as seen through SEM images, shows a rough surface that enhances photocatalytic efficiency by providing a larger surface area for reactions. The uniform distribution of TiO2 particles within the chitosan matrix is crucial for stable and efficient pollutant degradation during photocatalysis. Furthermore, Chitosan-TiO2 membranes offer a promising solution for batik wastewater treatment. They combine the benefits of chitosan's permeability and organic substance capture with TiO2's photocatalytic capabilities. This integration allows for efficient, one-step hybrid photocatalytic filtration, reducing the use of harmful chemicals and producing environmentally friendlier byproducts. Finally, AAS analysis demonstrated that the addition of TiO2 improved heavy metal degradation in batik waste, with optimal performance observed up to a 89.78% rejection rate, beyond which TiO2 agglomeration occurred.